Behavior and physiology in female Cricetulus barabensis are associated with the expression of circadian genes - Zhu, Hanyi; Wu, Ming; Mou, Junjie; Yang, Xueqi; Xu, Qian; Zhang, Yongjian; Zhang, Hao; Wang, Xinran; Xue, Huiliang; Xu, Jinhui; Chen, Lei; Xu, Laixiang (Frontiers in Endocrinology, 2024)
The circadian clock regulates the behavior, physiology, and metabolism of mammals, and these characteristics, such as sleep-wake cycles, exercise capacity, and hormone levels, exhibit circadian rhythms. Light signaling is the main stimulator of the mammalian circadian system. The photoperiod regulates the reproductive cycle of seasonal breeding animals, and the circadian clock plays a pivotal role in this process. However, the role of the clock in coordinating animal behavior and physiology in response to photoperiodic changes needs further investigation. The present study investigated the changes and correlation of behavioral activities, physiological indicators, and gene expression in female striped hamsters (Cricetulus barabensis) within 24 h under a 12L:12D photoperiod. We found that the daily rhythms of sleep-wake and open field were significant in hamsters. The expression of clock genes, melatonin receptor genes, and genes involved in general metabolism oscillated significantly in central and peripheral tissues (brain, hypothalamus, liver, ovary, and thymus) and was significantly associated with behavior and physiology. Our results revealed that the neuroendocrine system regulated the rhythmicity of behavior and physiology, and central and peripheral clock genes (Bmal1, Clock, Per1, Per2, Cry1, and Cry2), melatonin receptor genes (MT1, MT2, and GPR50), and metabolizing genes (SIRT1, FGF21, and PPARα) played important roles. Our results suggest that central and peripheral circadian clocks, melatonin receptors, and genes involved in general metabolism may play key roles in maintaining circadian behavior and metabolic homeostasis in striped hamsters. Our results may have important implication for rodent pest control.